2010
DOI: 10.1007/s00044-010-9473-4
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycaemic and aldose reductase inhibitory potential of Acacia catechu hard wood and Tectona grandis leaves

Abstract: The ethanolic extract of Acacia catechu hard wood (Ac) and the ethanolic as well as aqueous extracts of Tectona grandis leaves (Tg) showed marked antihyperglycaemic activity in both normoglycaemic and streptozotocininduced diabetic rats at 250 mg/kg dose levels. The ethanolic and aqueous extracts of Ac and Tg also showed marked inhibition on AR from eye lens of normal rats with IC 50 values of 9.30 and 9.08 and 3.05, 4.51 lg/ml, respectively. The ethanolic as well as aqueous extracts of both Ac and Tg also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The antihyperglycemic activity of an A. catechu ethanolic bark extract has also been demonstrated in alloxaninduced diabetic rats (Jarald et al, 2009). Bhatia et al (2011) have also shown that an ethanol extract of A. catechu hardwood exhibits antihyperglycemic activity in streptozotocin-induced diabetic rats at a dose of 250 mg/kg. Furthermore, the extract showed marked inhibition of aldose reductase enzyme activity in the eye lens of normal rats.…”
Section: Animal Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…The antihyperglycemic activity of an A. catechu ethanolic bark extract has also been demonstrated in alloxaninduced diabetic rats (Jarald et al, 2009). Bhatia et al (2011) have also shown that an ethanol extract of A. catechu hardwood exhibits antihyperglycemic activity in streptozotocin-induced diabetic rats at a dose of 250 mg/kg. Furthermore, the extract showed marked inhibition of aldose reductase enzyme activity in the eye lens of normal rats.…”
Section: Animal Studiesmentioning
confidence: 91%
“…Bhatia et al () have also shown that an ethanol extract of A. catechu hardwood exhibits antihyperglycemic activity in streptozotocin‐induced diabetic rats at a dose of 250 mg/kg. Furthermore, the extract showed marked inhibition of aldose reductase enzyme activity in the eye lens of normal rats.…”
Section: Animal Studiesmentioning
confidence: 96%
“…Future extension of these studies is the driving force behind the search for phytochemical and synthetic compounds such as flavonoids, chalcones, polyhydroquinolines, propiophenone derivatives, deoxyandrographolides, and thiazolidin-4-one derivatives. All of these have shown protective effects in mouse models of diabetes mellitus [285][286][287][288][289][290][291][292][293][294][295][296][297] and can be further tested and potentially utilized in the treatment of diverse forms of cancer cell progression and metastasis.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…Bhatia et al 55 reported that oral administration of ethanolic extract of A. catechu hard wood at 250 mg/kg elicits significant antihyperglycemic…”
Section: Pharmacological Activities Of Some Anti-diabetic Plantsmentioning
confidence: 99%